A espiritualidade no processo de trabalho de uma equipe interdisciplinar que atua em cuidados paliativos. - Arrieira, Isabel Cristina de Oliveira (2009)
This work aimed to build the meaning of spirituality for the interdisciplinary group that takes care of people suffering from cancer through palliative care. That group participates in the Oncologic Interdisciplinary Home Admission to hospital program (PIDI), from the individual building of spirituality of each member of the group. It is about a research with a qualitative, descriptive and exploratory approach. It had Vygotsky´s Historical-Cultural Theory as a theoretical reference. Vygotsky identifies two levels of development: one is about the achievements already reached which he calls level of real or effective development and the other one is the level of potential or proximal development, which relates to the capacities on the point of being built. Eight professionals from that group participated in the research. Data collection was carried out through the focal group technique, in a total of five meetings from which the following themes appeared: meaning of spirituality: individual building; spirituality: palliative care and death; spirituality: as a harmonizing element and an opportunity of group learning; an approach about spirituality during the building and meaning of spirituality for the oncologic PIDI group. After analyzing and reflecting about the data I could notice that when we take care of people who suffer from cancer through palliative care it is essential to include a spiritual approach for every member of the interdisciplinary group. This study was an important device to develop the abilities of most group members related to the spiritual approach in taking care of PIDI patients. As a result, another important fact that appeared was that most people in the group did not have any approach about spirituality in their education. That fact becomes a challenge to teaching institutions which focus care completeness most of the time. Among the meanings built by the group the inclusion of spirituality in patients´ care in palliative care means recognizing h man beings in their entirety, respecting their individualities besides acting as facilitators in the relationships between the users, their families and the group.